Está en la página 1de 15

# 9.

f ( x ) = f ( x0 ) + f ( x0 )( x x0 )
(n)
f ( x0 )
f
( x0 )
2
+
( x x0 ) + L +
( x x0 ) n
2
n!
f ( n+ 1 ) ( x 0 + q ( x x 0 ) )
+
( x x0 )n+1 (0 < q < 1).
( n + 1)!

n f ( x )
x x 0 ( x x 0 ) n

.
z = f ( x , y )( x 0 , y0 )
n + 1 , ( x 0 + h, y0 + h)
, f ( x0 + h, y0 + k )
h = x x 0 , k = y y0 n
r = h2 + k 2 0 r n

( t ) = f ( x0 + ht , y0 + kt ), (0 t 1).
(0) = f ( x0 , y0 ), (1) = f ( x0 + h, y0 + k ).

1
(1) = (0) + (0) + (0) + L
2!
1 (n)
1
+ ( 0) +
( n + 1) ( ), (0 < < 1).
n!
( n + 1)!

(*)

(t ),

( t ) = hf x ( x0 + ht , y0 + kt ) + kf y ( x0 + ht , y0 + kt )

= h + k f ( x0 + ht , y0 + kt ),
y
x

( t ) = h2 f xx ( x0 + ht , y0 + kt )
+ 2hkf xy ( x0 + ht , y0 + kt ) + k 2 f yy ( x0 + ht , y0 + kt )
LL LL
( n + 1) ( t ) =

n+1

p=0

p
p n +1 p
h
k
n+1

= h + k
y
x

n+1 p
p

x y

n + 1 p ( x 0 + ht , y 0 + kt )

n+1

f ( x 0 + ht , y 0 + kt ).

( 0) = f ( x 0 , y 0 ) , (1) = f ( x 0 + h, y0 + k )
(t ) n t = 0 ,

( n+1 ) ( t ) t = q (*).

f ( x0 + h, y0 + k ) = f ( x0 , y0 ) + h + k f ( x0 , y0 )
y
x
2

+ h + k f ( x 0 , y0 ) + L
2! x
y
n

+ h + k f ( x0 , y0 ) + Rn ,
(1)
n! x
y

n +1
1

Rn =
h + k f ( x0 + qh, y0 + qk ),
( n + 1)! x
y

## (0 < q < 1).

( 2)

(1) f ( x , y ) ( x 0 , y0 ) n
, Rn ( 2) .

z = f ( x , y ) ( x 0 , y 0 )
n + 1 , ( x 0 + h, y 0 + k )
,

f ( x 0 + h, y 0 + k ) = f ( x 0 , y 0 ) + h + k f ( x 0 , y 0 )
y
x
2

1

1

+ h + k f ( x 0 , y 0 ) + L + h + k f ( x 0 , y 0 )
2! x
y
n! x
y
1

h + k
+
( n + 1)! x
y

n+1

f ( x 0 + h, y 0 + k ),

Rn = o( r n ) ( r = h2 + k 2 )

(0 < < 1)

h + k f ( x 0 , y0 )
y
x
hf x ( x0 , y0 ) + kf y ( x0 , y0 ),
2

h + k f ( x 0 , y0 )
y
x

h2 f x x ( x0 , y0 ) + 2hkf xy ( x0 , y0 ) + k 2 f yy ( x0 , y0 ),
m

, h + k f ( x0 , y0 )
y
x
m

C
p= 0

h k

m p

p
p
m p
x y

( x0 , y0 )

, Rn
( x 0 , y0 ) M .
, :

M
M
n+ 1
n +1
n +1
(h + k ) =
Rn
r ( cosa + sina )
(n + 1)!
(n + 1)!

(
2)
=

n +1

(n + 1)!

M r n +1 ,

2
2
r = h + k .

( 3)

( 3) , Rn r 0 r n
.

n = 0 , (1)

f ( x0 + h, y0 + k )
= f ( x0 , y0 ) + hf x ( x0 + qh, y0 + qk )
+ kf y ( x0 + qh, y0 + qk )
.
f ( x , y ) f x ( x , y ) , f y ( x , y )
, f ( x , y )
.

(1) , x0 = 0, y0 = 0 ,
(1)n .

f ( x , y ) = f (0,0) + x
+ y f (0,0)
y
x
2

1

1

+ x
+ y f (0,0) + L + x
+ y f (0,0)
2! x
y
n! x
y
1

x
+
+ y
( n + 1)! x
y

n+1

f (x , y ),
(0 < q < 1) (5)

f ( x , y ) = ln(1 + x + y )
.

1
f x ( x, y) = f y ( x, y) =
,
1+ x + y

1
f xx ( x , y ) = f xy ( x , y ) = f yy ( x , y ) =
,
2
(1 + x + y )
3 f
2!
=
,
( p = 0,1,2,3),
p
3 p
3
x y
(1 + x + y )
4 f
3!
=
,
p
4 p
4
x y
(1 + x + y )

( p = 0,1,2,3,4),

x + y f (0,0) = xf x (0,0) + yf y (0,0) = x + y ,
y
x
2

x + y f (0,0)
y
x
= x 2 f xx (0,0) + 2 xyf xy (0,0) + y 2 f yy (0,0)
= ( x + y )2 ,
3

x + y f (0,0) = x 3 f xxx (0,0) + 3 x 2 yf xxy (0,0)
y
x
+ 3 xy 2 f xyy (0,0) + y 3 f yyy (0,0) = 2( x + y )3 ,

f ( 0 ,0 ) = 0 ,

1
1
2
ln(1 + x + y ) = x + y ( x + y ) + ( x + y )3 + R3 ,
2
3

R3 = x + y f (qx ,qy )
4! x
y
1
( x + y )4
=
,
(0 < q < 1).
4
4 (1 + qx + qy )

2 (0,0 )
f ( x , y ) = 1 x 2 y 2
f ( x0 + h, y0 + k ) = f ( x0 , y0 ) + f x ( x0 , y0 )h + f ( x0 , y0 )k
+

1
[ f x ( x0 , y0 )h 2 + 2 f xy ( x0 , y0 )hk + f y ( x0 , y0 )k 2 ] + o( r n )
2!
x
f x ( 0 ,0 ) = [
]
=0
f (0,0) = 1
2
2 ( 0, 0 )
1 x y
y2 1
f y (0,0) = 0
f x (0,0) = [
]
= 1
3 ( 0,0 )
(1 x 2 y 2 ) 2
xy
f xy (0,0) = [
]
=0
f y (0,0) = 1
3 ( 0, 0 )
(1 x 2 y 2 ) 2
2

f ( x 0 + h, y 0 + k ) = f ( x 0 , y 0 ) + f x ( x 0 , y 0 ) h + f ( x 0 , y 0 ) k
1
+ [ f x 2 ( x 0 , y 0 )h 2 + 2 f xy ( x 0 , y 0 )hk + f y 2 ( x 0 , y 0 )k 2 ]
2!
+ o( 2 )

h = x , k = y
1
1 x y = 1 + ( 1 x 2 y 2 ) + o( r 2 )
2!
2

r=

x2 + y2 0